The modification of social space as a tool for lowering social stress - Oded Stark (University of Bonn, Center for Development Research (ZEF), 2024)
The social stress experienced by an individual from having a low relative income or from having a low income-based rank is a derivative of the individual's location in social space, and is the outcome of unfavorable comparisons with other individuals in that space. (The term social space stands for the set of individuals with whose incomes or with whose income-based ranks the individual compares his income or his income-based rank.) The stress that arises from unfavorable social comparisons can cause physical and mental harm. Essentially, there are three ways to thwart unfavorable income-related comparisons experienced by an individual: to operate on the individual's income or on a characteristic (an attribute) of the individual's income; to operate on the incomes or on a characteristic of the incomes of the individual's comparators; or to modify the individual's social space. The first two approaches feature extensively in the existing literature. The third does not. In this communication, I analyze this third approach, keeping in mind its application as a policy tool for lowering social stress.
Keywords: D01; D63; D91; I10; I14; I31; Z18; 330; Social space; Unfavorable income-related comparisons; Low relative income; Low income-based rank; Social stress; Adverse health outcomes; Forming a health-related policy